1992
DOI: 10.1143/jjap.31.4301
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Acid Generation Reactions in Chemically Amplified Resists for Electron Beam and X-Ray Lithography

Abstract: The radiation-induced reactions of onium salts in some kinds of solutions and model compound solutions of chemically amplified electron beam (EB) and X-ray resists have been studied by means of picosecond and nanosecond pulse radiolysis. The following reaction mechanisms of the chemically amplified EB and X-ray resists have been elucidated. The radiation-induced reaction mechanisms are complicated due to the presence of several proton donors. The onium salts directly produce small amounts of Brønsted acids by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
230
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(232 citation statements)
references
References 10 publications
2
230
0
Order By: Relevance
“…The difference between EB and EUV resists is the energy absorption processes. [7][8][9] The EB-and EUV-induced radiation chemistry in CARs has been discussed from the perspective of the configuration of spurs, acid yield, and acid distribution. 10 Recently our research group found that the resist sensitivity in the EUV/soft X-ray region can be estimated from the exposure results at any wavelength in this region 11,12 and also from the exposure results for EB.…”
Section: -5mentioning
confidence: 99%
“…The difference between EB and EUV resists is the energy absorption processes. [7][8][9] The EB-and EUV-induced radiation chemistry in CARs has been discussed from the perspective of the configuration of spurs, acid yield, and acid distribution. 10 Recently our research group found that the resist sensitivity in the EUV/soft X-ray region can be estimated from the exposure results at any wavelength in this region 11,12 and also from the exposure results for EB.…”
Section: -5mentioning
confidence: 99%
“…From the results of our research, the reaction mechanisms of the acid generation have been proposed for EB and Xray CA resists [6]. It is proposed that the main reaction path of the acid generation is considered to be the path through the ionization of a matrix polymer because the energy of the ionizing radiation is absorbed mostly by the matrix polymer.…”
Section: Introductionmentioning
confidence: 93%
“…In the presence of sulfonium salt, the electrons and radical anions (CH3CN') are scavenged through the one-electron reduction of the onium salts [6,10,11 ], and the salts are decomposed (reaction (4) and (5)):…”
Section: Contribution Of Ionization Process To the Acid Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the key difference between conventional and chemically amplified resist systems and causes problems specific to chemically amplified resists. One aspect that has s storng influence on lithographic performance is the deactivation of catalytic acid by air-borne contaminants during exposure and PEB [4][5][6][7][8]. The influence of a small amount of Nmethylpyrollidone (NMP) on the formation of insoluble layers has already been reported.…”
Section: Introductionmentioning
confidence: 99%